Integrated peanut aflatoxin management for increase income and nutrition in northern Ghana - Sugri, I.; Osiru, M.; Abudulai, M.; Abubakari, M.; Asieku, Y.; Lamini, S.; Zakaria, M. (Informa UK Limited, 2017)
Aflatoxins contamination in peanut seeds remains a major challenge in Ghana. This study evaluated aflatoxin levels in peanut samples from farmer storage units, and participatory on-farm research trials. In all, 240 respondents were covered from six main producing districts in northern Ghana through a multi-stage sampling approach. Samples were analysed for total aflatoxins using the indirect Enzyme Linked Immunosorbent Assay technique. Overall, total aflatoxins in the farmer stored nuts showed wide variations across communities and districts. At 20 ppm permissible level, 92.9% of samples (n = 240) from farmer stored peanuts and 98.7% of samples (n = 150) from the on-farm demonstrations were classified as safe at 4–8 weeks after harvest. Therefore, sustainable reduction of aflatoxins to safe limits is possible through greater collaboration among the value chain actors. Low-cost good agricultural practices within the remit of the growers should be prioritized alongside public awareness programmes.